The scope and role of industrial engineer for management and decision at world of organizations - Acevedo Borrego, Adolfo (2012)
industrial engineer for decision making arising from the new managerial role and the challenges of environment and different orientations to the perception of problems, choice of alternatives and optimization of results. There are several directions to focus the company, they are structure, process, person and time, the first includes techniques that lead to optimal results, the second considers the functionality, comprises the classical, neoclassical, strategic process, the third considers human relationships, behavior, knowledge management, the latter comprises the change, organizational development, evolution and technological innovation, contingency and strategy. They cater to partial, suggesting incomplete solutions due to a skewed definition of problem. The new business environment, it requires the management of organizations deal comprehensively with the dimensions and elements that affect performance and results. In this sense, the holistic approach of industrial engineer, provides a conceptual framework for the investigation of problems, identification of problematic situations, evaluation criteria and choice, decision and implementation of actions leads to expected results, depending on the lens and results emerging, synergies or failures.